Close insight into the nature of intermolecular interactions in dihydropyrimidine-2(1H)-thione derivatives. Issue 11 (23rd February 2017) - Saeed, Aamer; Flörke, Ulrich; Fantoni, Adolfo; Khurshid, Asma; Pérez, Hiram; Erben, Mauricio F.
Abstract : The cyclic pyrimidine-thione synthon was characterized via a complete analysis of intermolecular interactions for a series of twelve closely related dihydropyrimidine-2(1 H )-thiones. Abstract : The crystal structures of four 1-( R -phenyl)-4, 4, 6-trimethyl-3, 4-dihydropyrimidine-2(1 H )-thione derivatives [ R = 2-chloro (1 ), 2, 3-di-chloro (2 ), 2, 4-di-methyl (3 ), and 4-methoxy (4 )] were determined and analysis of their molecular conformations was carried out. A comparative study of the intermolecular interactions—including eight closely related structures from CSD—was performed and the degree of isostructurality was quantified. The intermolecular interactions were characterized in terms of the periodic system electron density and the topological analysis highlighted the role of N–H⋯SC hydrogen bonds in the stabilization of the different supramolecular architectures. PIXEL lattice energy calculations revealed that the dispersion component was the major contributor, together with the important role of the Coulombic term to the total energy. The interaction energies for molecular pairs involving N–H⋯SC hydrogen bonds indicated a dominant contribution to packing stabilization coming from the Coulombic components. Hirshfeld surfaces and fingerprint plots allowed us to visualize different intermolecular contacts and their relative contributions to the total surface for each compound. Analysis of the electrostatic potentials (ESP) correlated well with the computed energies, thus characterizing the strengths of the different interactions.